2000
DOI: 10.1093/jac/45.1.57
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo influence of adjunct clarithromycin on the treatment of mucoid Pseudomonas aeruginosa

Abstract: Recent in vitro and in vivo data have substantiated the beneficial effects of macrolides/ azalides for use against Pseudomonas aeruginosa. While macrolides/azalides are not very potent in vitro antimicrobial agents against this pathogen, they appear to have an adjunctive role by either altering the course of infection owing to their inhibition of biofilm production or modulation of the host anti-inflammatory response, or both. To determine the in vitro and in vivo effects of clarithromycin as adjunctive therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The ideal approach to conditions found in CF patients would be the use of in vivo models as already described [44,45]. Using mouse models of P. aeruginosa respiratory infections, a synergistic activity was reported with a 5-day oral administration of clarithromycin (100 mg/kg/day) + ceftazidime (1500 mg/kg/day) [44] and a 7-day oral administration of clarithromycin (10 mg/kg/day) + levofloxacin (10 mg/kg/day) [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal approach to conditions found in CF patients would be the use of in vivo models as already described [44,45]. Using mouse models of P. aeruginosa respiratory infections, a synergistic activity was reported with a 5-day oral administration of clarithromycin (100 mg/kg/day) + ceftazidime (1500 mg/kg/day) [44] and a 7-day oral administration of clarithromycin (10 mg/kg/day) + levofloxacin (10 mg/kg/day) [45].…”
Section: Discussionmentioning
confidence: 99%
“…Using mouse models of P. aeruginosa respiratory infections, a synergistic activity was reported with a 5-day oral administration of clarithromycin (100 mg/kg/day) + ceftazidime (1500 mg/kg/day) [44] and a 7-day oral administration of clarithromycin (10 mg/kg/day) + levofloxacin (10 mg/kg/day) [45]. The two studies showed that co-administration of antibiotics in these cases allowed improvement of biofilm destruction compared with single drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…It would be important to detect the minimal concentration showing significant killing in biofilms. Recently, it was shown that increasing concentrations (32 or 128 Ìg/ml) of clarithromycin had a synergistic or additive effect in timekill experiments for mucoid-producing P. aeruginosa [29]. However, it would be less applicable to clinical management of patients if any antibiotic had good bactericidal activity only at much higher concentrations than clinically achievable concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Gram-negative bacteria attach primarily by means of proteinaceous appendages known as fi mbriae and pili, with other antibiotics. [53][54][55] In regard to the direct killing activity of macrolides against P. aeruginosa, we have reported reduction of the viability of this organism when the bacteria were incubated with macrolides for prolonged times. 14 Exposure to azithromycin for 48 h or more significantly decreased the viability of P. aeruginosa PAO1 in a concentration-dependent manner, whereas no effect on viability was observed with 24 h or less incubation with macrolide.…”
Section: Bacterial Cell-surface Structures and Adherence To Host Cellsmentioning
confidence: 99%